Effect of Extracellular Vesicles Derived From Lactobacillus plantarum Q7 on Gut Microbiota and Ulcerative Colitis in Mice - Hao, Haining; Zhang, Xinyi; Tong, Lingjun; Liu, Qiqi; Liang, Xi; Bu, Yushan; Gong, Pimin; Liu, Tongjie; Zhang, Lanwei; Xia, Yongjun; Ai, Lianzhong; Yi, Huaxi (Frontiers in Immunology, 2021)
Probiotics plays an important role in regulating gut microbiota and maintaining intestinal homeostasis. Extracellular vesicles (EVs) derived from probiotics have emerged as potential mediators of host immune response and anti-inflammatory effect. However, the anti-inflammatory effect and mechanism of probiotics derived EVs on inflammatory bowel disease (IBD) remains unclear. In this study, the effect of Lactobacillus plantarum Q7-derived extracellular vesicles (Q7-EVs) on gut microbiota and intestinal inflammation was investigated in C57BL/6J mice. The results showed that Q7-EVs alleviated DSS-induced colitis symptoms, including colon shortening, bleeding, and body weight loss. Consumption of Q7-EVs reduced the degree of histological damage. DSS-upregulated proinflammatory cytokine levels including IL-6, IL-1β, IL-2 and TNF-α were reduced significantly by Q7-EVs (p < 0.05). 16S rRNA sequencing results showed that Q7-EVs improved the dysregulation of gut microbiota and promoted the diversity of gut microbiota. It was observed that the pro-inflammatory bacteria (Proteobacteria) were reduced and the anti-inflammatory bacteria (Bifidobacteria and Muribaculaceae) were increased. These findings indicated that Q7-EVs might alleviate DSS-induced ulcerative colitis by regulating the gut microbiota.